LGBTQIA+ Elderly: How male gay men are affected by etarism - Paula, Victor Barbosa de; Bana , Cesar Augusto (Seven Editora, 2023)
The elderly population (60 years or older) is the fastest growing in Brazil. By 2060 these individuals will represent a quarter of the Brazilian population, at least 25.5%, according to IBGE (Brazilian Institute of Geography and Statistics) data from 2018. For this reason, both political, social, psychological, and health issues, as well as Geriatrics and Gerontology intensify their assessment and methodology, to adapt to all these problems that grow exponentially over time (Camarano and Kanso, 2010). The present work seeks to develop research related to how the different prejudices (homophobia and etatism) directed to the people of this population affected/affect their future, their present, and their past with a focus on the LGBTQIA+ population, focusing on the cut of gay men of this community, to understand how these people lived and how they were of Homophobia in times when they needed to hide their sexuality, how it affected or affects the way they perceived themselves back then and how they perceive themselves today, being elderly people and being within the LGBTQIA+ community, through semi-structured online entertainment. The adversities in the living conditions that this population faces can cause serious psychological problems, adding this to the lack of knowledge and research in this area, explains that aging within the the LGBTQIA+ community is an aspect of this population that needs to be discussed and studied, thus contributing to a better quality of life and aging of these people, without stigmas or prejudices. DOI:https://doi.org/10.56238/devopinterscie-160